Audit Quality Elements And Auditor Performance In Pakistan: An Empirical Evidence - Abubakar Shafiq (Migration Letters, 2024)
This paper aims to investigate some elements that are necessary to improve the quality of government auditors’ audits. In Pakistan, the quality of audits is insufficient to attract public confidence in governmental functionaries. This evidence proves the underperformance of government audit personnel. The current survey assesses the influence [1]of top management support, career planning, effort and reward fairness, and employee participation on auditor performance, focusing on audit quality elements that the Pakistan Audit Department has not sufficiently studied. The study revealed the positive significance of higher management support, effort & reward fairness, and employee participation. On the other hand, the impact of career planning on auditor performance was not significant. The researcher first applied the EFA method to extract potential factors. Subsequently, the results were validated using OLS regression techniques.